Effect of expander-extruder processed complete diet containing sugarcane bagasse on growth and nutrient utilization in Ongole bull calves - REDDY, G V N; REDDY, K JOJI; NAGALAKSHMI, D (The Indian Journal of Animal Sciences, 2014)
Sugarcane bagasse was incorporated as sole source of roughage (40%) in complete diet and then processed into mash. Half of the mash was subjected to expander-extruder processing to form pelleted feed. Both fonns (mash and pellet) of the diet were compared with conventional form based on concentrate mixture and sugarcane bagasse as such in the ratio of 60: 40. These feeds were fed individually to 18 Ongole bull calves (6 in each group) for 180 days duration in a growthcum- metabolic trial using completely randomized design. The DM and water intakes were comparable on all the diets. The digestibilities of DM, OM, CP, NFE were higher on complete diets compared to conventional diet. Among the complete diets, nutrients were efficiently digested in pelleted form than that in mash form. Pelleted diet group recorded higher nitrogen balance compared to other groups. All the groups were on positive nitrogen, calcium and phosphorus balances. The DCP and TDN contents of diet were found higher due to expander-extruder pelletization. Average daily gain and feed efficiency was significantly higher on pelleted diet. The cost of feed/kg gain was reduced due to expanderextruder peiletization. These results suggested that blending of concentrates and roughage into complete diet and its pelleting improved palatability and nutrient utilization.